2020
DOI: 10.31744/einstein_journal/2020ao5227
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a behavior change program on cardiovascular parameters in patients with hypertension: a randomized controlled trial

Abstract: Objective: To investigate the efficacy of a behavior change program named Vida Ativa Melhorando a Saúde on cardiovascular parameters in hypertensive patients. Methods: Ninety hypertensive patients aged over 40 years were randomly allocated to one of two groups: Vida Ativa Melhorando a Saúde or Control (n=45 respectively). Patients in the Vida Ativa Melhorando a Saúde group took part in a behavior change program aimed to encourage changes in physical activity levels and eating habits, according to the Social Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…However, the intervention was done only for 6 months and this period was considered to be suboptimal to observe any behavior change or even to maintain it. Studies suggested that desirable behavior change seemed to be more likely to observe in 12 months or more, especially conducted in developing countries (23,24). Therefore, longer observation is needed to get further information regarding patients' compliance and complications occurred.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervention was done only for 6 months and this period was considered to be suboptimal to observe any behavior change or even to maintain it. Studies suggested that desirable behavior change seemed to be more likely to observe in 12 months or more, especially conducted in developing countries (23,24). Therefore, longer observation is needed to get further information regarding patients' compliance and complications occurred.…”
Section: Discussionmentioning
confidence: 99%
“…endothelial inflammation, improved oxidative-antioxidant balance and a higher level of NO bioavailability [26].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarises the characteristics of the included studies. Of the twenty included studies, 12 were randomised controlled trials (RCTs) [45][46][47][48][49][50][51][52][53][54][55][56], seven were quasiexperimental studies [57][58][59][60][61][62][63], and one was a secondary analysis of trial data. All included studies were published between 2002 and 2022.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%